The Cavendish Home for Boys and Girls - Legrand, Claire, 1986- (Simon & Schuster Books for Young Readers, 2012)
Practically-perfect twelve-year-old Victoria Wright must lie, sneak, and break the rules when her investigation of the disappearance of her best--and only--friend, Lawrence, reveals dark secrets about her town and the orphanage run by the reclusive Mrs. Cavendish.